Factors Associated with Hearing Loss in Helicopter Aircrew of Indonesian Army Aviation Center, Semarang - Muyassaroh, Muyassaroh; Sayuti, Fajri Imam; Ruspita, Dian Ayu; Dewi, Anna Mailasari kusuma; Budiarti, Rery; Naftali, Zulfikar; Widodo, Pujo (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: Hearing loss and tinnitus may occur in pilots due to exposure of the high noise level (ranges from 104-110 dB) generated by aircraft/helicopters. In addition, flying time, acoustic trauma, diabetes mellitus, hypertension and smoking are risk factors of hearing loss. Objective: to identify the factors associated with hearing loss in the crew of the Indonesian Army Aviation Center, SemarangMethods: in the cross-sectional research, 114 military helicopter aircrews aged 20-58 years, working for the Army Aviation Center in Semarang were included. The exclusion criteria were history of previous ear surgery, infection of the outer and middle ear, the use of ototoxic drugs (kanamycin, cisplatin and carboplatin). The level of hearing loss and tinitus was assessed by otoscopy and audiometry. Whereas, tinnitus was obtained from the history taking. Data were analyzed using chi-square test and fisher's exact and Yates’s correction.Results: One hundred and fourteen subjects (mean age of 26.54 + 4.72) were included. Several factors such as flight time (p = 0.698), acoustic trauma (p = 0.151), diabetes mellitus (p = 0.596), smoking (p = 0.222), hypertension (p = 0.356) were not associated with sensorineural hearing loss. Several factors such as flight time (p = 0.706), acoustic trauma (p = 0.5160), diabetes mellitus (p = 0.789), smoking (p = 0.495), hypertension (p = 0.112) were not associated with tinnitus.Conclusion: There is no association between flight time, acoustic trauma, diabetes mellitus, hypertension, and smoking and hearing loss.